Cystic plate approach in laparoscopic cholecystectomy: a consecutive retrospective analysis - Zhou, Yanjie; Xiao, Le; Luo, Zhulin; Luo, Hao; Tan, Zhen; Wang, Tao (Frontiers in Surgery, 2024)
PurposeThis study aimed to investigate the safety, feasibility, and possible advantages of the cystic plate approach during laparoscopic cholecystectomy in a retrospective cohort of surgical patients.MethodsWe summarized the key points of the technical approach, retrospectively analyzed the clinical outcomes of 156 patients in the cystic plate approach group from July 2018 to July 2023, and compared the findings with those of 173 cases in the routine approach group from the same period.ResultsWe observed no differences in the average stone size, operation time, postoperative hospital stay, conversion rate, complications, or Visual Analog Scale pain scores on the second day of surgery between the two groups (p = 0.076, 0.067, 0.278, 1.000, 0.633, and 0.131, respectively). However, intraoperative blood loss, number of clips used, volume of postoperative drainage fluid, and Visual Analog Scale pain scores on the day of surgery in the cystic plate approach group were significantly lower than those in the routine approach group (p = 0.000, 0.031, 0.027, and 0.021, respectively).ConclusionsThe cystic plate approach is a safe, feasible, and effective approach that has the advantages of minimal invasiveness with less bleeding and seepage, reduced use of biological clips, and less pain, potentially minimizing the risk of iatrogenic biliary injury. Trial registrationThis study was registered at the International Clinical Trial Registry (ChiCTR2100052860). Registration date: November 6, 2021.